The Evolution of Welfare Systems: Social Democratic and Social Autocratic Paths - Levai, Imre (Competitio, 2009)
Students of global and regional political economy have produced a vast literature on divergent paths of capitalist evolution. The evolution of welfare systems, in general, and their different paths, in particular, have also widely been analysed in economic and social studies. The author, joining the discussions from a world system perspective, makes an attempt at presenting a global and regional political economic comparison of the seemingly similar welfare systems that have evolved in Northern and in Eastern Europe. The apparent convergence of the Sovietic type to the Nordic social democratic pattern is scrutinised, distinguishing it from the latter by the “social autocratic” label. Journal of Economic Literature (JEL) kód: I31, I38, P36, P38